2003
DOI: 10.1007/s00213-002-1332-7
|View full text |Cite
|
Sign up to set email alerts
|

Startle magnitude and prepulse inhibition: effects of alcohol and attention

Abstract: These findings suggest that both startle magnitude and PPI are increased by attention and that failure to control for the effects of attention on control trials may result in an underestimation of the effect of attention on PPI. Furthermore, the effect of alcohol on attention does not appear to generalize to the voluntary attentional processes involved in the attentional modulation of PPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Moreover, a significant association between startle magnitude after alcohol consumption and the frequency of drinking alcohol has been shown [70]. The acoustic startle reflex also seems to be reduced in sons of alcoholics, independently of comorbid anxious disorders [179].…”
Section: The Startle Responsementioning
confidence: 96%
“…Moreover, a significant association between startle magnitude after alcohol consumption and the frequency of drinking alcohol has been shown [70]. The acoustic startle reflex also seems to be reduced in sons of alcoholics, independently of comorbid anxious disorders [179].…”
Section: The Startle Responsementioning
confidence: 96%
“…For instance, ethanol administration was observed to disrupt PPI in ethanol-preferring (P) but not in non-preferring (NP) rats (Jones et al 2000). In humans, ethanol has been reported to be associated with a disruption of PPI (Hutchison et al 2003;Grillon et al 2000), an effect found by the Grillon et al (2000) group only among children of alcoholics and not among control subjects. Given the age-related vulnerability of adolescents to high levels of ethanol consumption, the present study was designed to test the hypothesis that adolescent animals might be more sensitive to ethanolinduced disruption of PPI than adult animals.…”
Section: Introductionmentioning
confidence: 95%
“…Based on the hypothesis that nicotine facilitates information processing and attention, we predicted that the abstinent smokers would show reduced PPI compared to the two other groups. In addition, because PPI is affected by attention to the prepulse, we built an attend/ignore-the-prepulse instruction into the design of the present study (Hutchison et al 2003) …”
Section: The Present Studymentioning
confidence: 99%